A Grid-Powered Framework to Support Courses on Distributed Programming - Maggi, Paolo; Sisto, Riccardo (IEEE transactions on education, 2007)
Grading programming assignments of courses on distributed programming can greatly benefit from extensive testing, especially if quality aspects such as portability, robustness, security, and performance have to be evaluated. This paper presents a framework that was developed at the Turin Polytechnic, Turin, Italy, to enable seamless and fast implementation of Web portals for automated management of student programming assignments. By using a computational grid facility to schedule testing jobs on different hosts, the framework offers high flexibility and scalability, thus enabling computationally intensive tests and some kinds of distributed tests, such as portability tests and field tests, which otherwise would be difficult to automate. The grid can be made of ordinary and even nondedicated or dismissed PCs, which, according to the authors' experience, is enough to offer students online extensive testing services. The framework was successfully used in two courses on distributed programming, located at different sites, partially overlapped in time, and attended by a total of 60 students. However, the framework should be scalable enough to work with increasing numbers of students and courses